2019
DOI: 10.1158/0008-5472.can-18-3143
|View full text |Cite
|
Sign up to set email alerts
|

Solid Tumor–Induced Immune Regulation Alters the GvHD/GvT Paradigm after Allogenic Bone Marrow Transplantation

Abstract: Growth of solid tumors is often associated with the development of an immunosuppressive tumor microenvironment (TME). It has been suggested that the influence of the TME may extend beyond the local tumor and results in systemic immunosuppression. Here, we utilize two murine cancer models to explore the influence of solid tumors on the occurrence of alloreactivity-driven GvHD and graft-versus-solid tumor (GvT) effects following MHC-mismatched allogeneic bone marrow transplantation (allo-BMT). Melanoma-or colon … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 48 publications
3
14
0
Order By: Relevance
“…One of the major factors hindering current cancer immunotherapies is the TME that impedes the anti-cancer adaptive immune response [1,2,3]. Previous work from our group demonstrated that the TME extends beyond the tumour and can result in systemic immunosuppression [5]. Hence, there is an urgent need to better understand the features of TME and to develop new therapeutic strategies to overcome the TME [4,5,6].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the major factors hindering current cancer immunotherapies is the TME that impedes the anti-cancer adaptive immune response [1,2,3]. Previous work from our group demonstrated that the TME extends beyond the tumour and can result in systemic immunosuppression [5]. Hence, there is an urgent need to better understand the features of TME and to develop new therapeutic strategies to overcome the TME [4,5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Before the harvesting of B16 cells, a trypsin–EDTA solution was added to the culture flask for 5 min at 37 °C in a 5% CO 2 to detach the tumour cells. Prior to their use, cells were tested for the presence of endotoxins with the LAL Chromogenic Endotoxin Quantitation Kit (Pierce) and for mycoplasma with PlasmoTest (InvivoGen) [5].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations